Laparoscopic adhesiolysis in a mini pony - Teixeira, Pedro Paulo Maia; Fidelis Junior, Otávio Luiz [UNESP]; Medeiros, Regina Mendes [UNESP]; Silva, Marco Augusto Machado; Coutinho, Leandro Nassar; Poló, Tatiana Silva [UNESP]; Marques, José Antônio [UNESP]; Vicente, Wilter Ricardo Russiano (My University, 2013)
Background: Intraperitoneal adhesions are common in equines, especially following exploratory celiotomy. Adhesiolysis is the treatment of choice for patients presenting postsurgical adhesions. Laparoscopic approach for adhesiolysis presents several advantageous aspects in human patients. The aim of the current study was to report a case of successful laparoscopic adhesiolysis in a mini pony horse. Case: A male Shetland Pony, weighing 140 kg, was admitted under complaint of right hind limb trauma and treated surgically for metatarsal fracture reduction. The patient has also had intermittent episodes of colic and was always treated clinically without major complications. The pony had no history of previous abdominal surgery and no episodes of acute abdomen were seen during hospital stay. Three months following ostheosynthesis, an exploratory laparoscopic approach was carried out to assess the possible cause or consequences of the episodes of acute abdomen. The patient was submitted to general anesthesia, positioned in dorsal recumbency and the abdomen was clipped and aseptically prepared for surgery. During the laparoscopic inspection, there were adhesions involving the ventral abdominal wall and a ventral mesogastric segment of duodenum. Laparoscopic adhesiolysis was performed using a two-port approach, by gently breaking the adhesion bands using meticulous traction with a 10-mm laparoscopic atraumatic Babcock forceps. Afterwards, the intestinal loop was rinsed with heparin sodium solution diluted in normal saline. The pneumoperitoneum was completely drained and the trocars sequentially withdrawn from the abdominal wall. The synthesis of the muscular layer was carried out using an interrupted cross mattress pattern, followed by synthesis of the skin with an interrupted cushion pattern. Total surgical time was 58 min. the patient was able to recover without complications. In the early postoperative period, the surgical recovery was considered excellent. No apparent adhesion involving the previously affected intestinal loop was found during the ultrasound exam following 15 days of surgery. Furthermore, the surgical wounds had healed completely, with no complications. Discussion: In the current case report, the primary cause of the acute abdomen episodes was not determined since the patient had never undergone abdominal surgery. It was hypothesized that an acute inflammation of the duodenal loop that was involved by the adhesion bands may have triggered the adhesiogenesis. Laparoscopy was efficient and presented a short operative time, due to magnification of image and adequate observation of structures surrounded by adhesion bands. Although the use of Babcock forceps is not usually recommended for adhesiolysis in the current literature, it was both effective in manipulating the bowel and performing the adhesiolysis. The heparin solution diluted in normal saline was effective in preventing the recurrence of new adhesions, which was evidenced by ultrasonography following 15 days. The laparoscopic approach usually minimizes the new formation of adhesions as trauma to the peritoneal surfaces is minimized by the use of delicate instruments, as observed in the current study. In addition, laparoscopy reduces the possibility of contact among the peritoneal surfaces and foreign bodies, such as gauze, glove powder and room air particles. Moreover, it maintains the abdominal surfaces in adequate humidity environment.
Keywords: Adhesiolysis; Endosurgery; Equines; Intraperitoneal adhesions.; Laparoscopy